2017
DOI: 10.1101/192765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivo, chromatin is a fluctuating polymer chain at equilibrium constrained by internal friction

Abstract: Chromosome mechanical properties determine DNA folding and dynamics, and underlie all major nuclear functions. Here we combine modeling and real-time motion tracking experiments to infer the physical parameters describing chromatin fibers. In vitro, motion of nucleosome arrays can be accurately modeled by assuming a Kuhn length of 35-55 nm. In vivo, the amplitude of chromosome fluctuations is drastically reduced, and depends on transcription. Transcription activation increases chromatin dynamics only if it inv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(64 reference statements)
3
2
0
Order By: Relevance
“…It is therefore tempting to link the coil-globule transition of chromosomes to the vanishing of the second virial coefficient of nucleosome-nucleosome interaction. This is also in line with quite recent measurements of chromosome dynamics in yeast, which has been modeled as a Rouse dynamics slowed down by nucleosomenucleosome transient interactions [29]. Following this line and going into more detail, inactive (black ) chromatin is very close to the Θ-point, indicating that nucleosomenucleosome interactions might be dominant within inactive domains.…”
Section: Comparison With Nucleosome Core Particles Solution Experimensupporting
confidence: 88%
See 2 more Smart Citations
“…It is therefore tempting to link the coil-globule transition of chromosomes to the vanishing of the second virial coefficient of nucleosome-nucleosome interaction. This is also in line with quite recent measurements of chromosome dynamics in yeast, which has been modeled as a Rouse dynamics slowed down by nucleosomenucleosome transient interactions [29]. Following this line and going into more detail, inactive (black ) chromatin is very close to the Θ-point, indicating that nucleosomenucleosome interactions might be dominant within inactive domains.…”
Section: Comparison With Nucleosome Core Particles Solution Experimensupporting
confidence: 88%
“…First, color -specific measures of the Kuhn length (in base pairs and in nanometers) of active, inactive and repressed domains respectively. Strikingly, these measures are on par with Hi-C data in mammals [34] as well as to most recent dynamic measurements in yeast [29]. The knowledge of both Kuhn lengths leads to the value of the compaction of the chromatin, i.e.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…We observed that the coefficient of diffusion of the trnascriptionaly activated HXK1 gene decreases independently of its interaction with the nuclear periphery. This is reminiscent of the confined motion of mRNA-producing genes observed in human cells 70 and agrees with the increased chromatin dynamics observed upon transcription arrest 71 . Transcriptional activation and the action of nucleosome remodelers have in other instances been shown to increase chromatin diffusion coefficient in yeast 72 .…”
Section: Despite This Precaution We Observed Large Cell-to-cell Varisupporting
confidence: 84%
“…In the absence of transcriptional activity, chromatin movements were no longer correlated independently of their constant, but small correlation length. Because protein and mRNA concentration as well as transient contacts and looping change during transcription, they also affect the mechanical properties of the chromatin fiber (20,44,45).…”
Section: Discussionmentioning
confidence: 99%